PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN SIKAP BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Yayuk Maya Sari; Syakdanur Nas; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to determine the effect of entrepreneurial knowledge and entrepreneurship attitude on entrepreneurial interest at economic education department university of riau. It’s using a quantitative descriptive approach, the population in the study is students who have taken entrepreneurship courses as many as 203 students and the population was taken as sample (purposive sampling). Data collection technique using document and questionnaires. The analysis of data was used path analysis. The result showed that the the entrepreneurial knowledge is in medium category, entrepreneurship attitude is in medium category, and entrepreneurial interest is in medium category.Key Words: Entrepreneurial Knowledge, Entrepreneurship Attitude, Entrepreneurial Interest